45th AIAA Fluid Dynamics Conference 2015
DOI: 10.2514/6.2015-3219
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cavity Oscillations via Three-Dimensional Steady Blowing

Abstract: This paper presents an investigation of open-loop control of cavity flow oscillations using a three-dimensional (3-D) array of steady jets located at the leading edge of the cavity. The actuation is introduced to suppress the fluctuating surface pressure in a rectangular cavity with a length-to-depth ratio (L/D) of 6 at Mach numbers from 0.3 to 0.7. Several different slot-jet configurations are assessed for their control performance considering the jet output momentum and interactions with the boundary layer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…The numerical results of the baseline flow at M ∞ = 0.6 and Re D = 10 4 have been compared to the results from the experiments at Re D = 3.3 × 10 5 . Good agreement is found concerning the properties of Rossiter modes as reported in the study by Zhang et al 33 (not shown here). Moreover, the time-averaged and Reynolds stress flow fields from the present work and the experiments exhibit qualitative agreement as shown in figure 2.…”
Section: Numerical Approachsupporting
confidence: 90%
See 4 more Smart Citations
“…The numerical results of the baseline flow at M ∞ = 0.6 and Re D = 10 4 have been compared to the results from the experiments at Re D = 3.3 × 10 5 . Good agreement is found concerning the properties of Rossiter modes as reported in the study by Zhang et al 33 (not shown here). Moreover, the time-averaged and Reynolds stress flow fields from the present work and the experiments exhibit qualitative agreement as shown in figure 2.…”
Section: Numerical Approachsupporting
confidence: 90%
“…For spanwise-periodic case at M ∞ = 0.6, the dominant and subdominant Rossiter modes based on the measurement from the aft wall are modes II and I, respectively. This phenomenon is also observed in experimental work from Zhang et al 33 with a higher Reynolds number for M ∞ = 0.6 cavity flow. However, the peaks of these two modes are significantly suppressed in the finite-span case.…”
Section: Probe Locationsupporting
confidence: 81%
See 3 more Smart Citations